Kontribusi Negara dan Masyarakat dalam Proses Demokratisasi di Indonesia - Putra, Bayu Karunia (Faculty of Social and Political Sciences, Universitas Swadaya Gunung Jati, 2022)
Rights and obligations are an important element to be maintained and cared for properly by the Indonesian people today. Because, related to the context of citizenship, rights and obligations are basic values that must exist for every citizen to build a good country and society in the future. This is because the current development of the state and society in Indonesia has given rise to various forms of problems that must be answered jointly related to the involvement of the state and society, especially in the process towards democratization in Indonesia. Apart from that, democratization can create a harmonious life for the future. Thus, through the process towards democratization, it can have a positive impact in all aspects of the life of the nation and state. The purpose of this study was to determine the involvement of the state and civil society in the process towards democratization in Indonesia, whether it was running according to expectations as mandated by Pancasila and the 1945 Constitution. The research method used was a literature study method, in which the sources and data obtained directly through journals, books, and other written sources. The results of this study show that the involvement of the state and civil society in the process towards democratization has improved in Indonesia today.